Implementation of Project-Based Learning in Improving Students' Problem-Solving in Chemistry Learning: A Systematic Literature Review - Halimatuzzahra, Halimatuzzahra; Louise, Isana Supiah Yosephine (Jurnal Pendidikan MIPA, 2025)
One of the 21st-century skills that needs to be developed is problem-solving. Problem-solving ability is understanding problems, planning solutions, applying solutions, evaluating, and finding solutions to problems. In fact, problem-solving ability in chemistry learning is still low, so a strategy is needed to overcome this problem, one of which is the application of project-based learning. Project-based learning is a learning model that involves students directly in the learning process through research activities. This study aims to evaluate the effect of implementing the Project-Based Learning (PjBL) model on students' problem-solving skills in learning chemistry. The method used is a Systematic Literature Review (SLR). Articles were obtained from Google Scholar, Scopus, and DOAJ, and 9 articles met the inclusion criteria set and were analyzed further. The results of the analysis show that the PjBL model has a positive influence on students' problem-solving skills. Project-based learning allows learners to be creative, work together, and develop solutions within a particular time, improving their collaboration, communication, and critical thinking skills. Implementing PjBL also provides a more interesting and realistic learning experience, helping learners understand the learning material and practice practical skills. Overall, implementing PjBL shows positive results in achieving chemistry learning objectives in cognitive, affective, and psychomotor domains.      Keywords: chemistry learning, problem-solving, project-based learning.